2014
DOI: 10.3390/rs6053624
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Complex Mountainous Forests with L-Band SAR and Landsat Data Integration: A Comparison among Different Machine Learning Methods in the Hyrcanian Forest

Abstract: Forest environment classification in mountain regions based on single-sensor remote sensing approaches is hindered by forest complexity and topographic effects. Temperate broadleaf forests in western Asia such as the Hyrcanian forest in northern Iran have already suffered from intense anthropogenic activities. In those regions, forests mainly extend in rough terrain and comprise different stand structures, which are difficult to discriminate. This paper explores the joint analysis of Landsat7/ETM+, L-band SAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 72 publications
(110 reference statements)
5
55
0
Order By: Relevance
“…It is also relatively simple to implement, requiring little user-intervention; an advantage that is frequently noted [34][35][36]. This is of relevance to this research, since compared to other non-parametric approaches, including Neural Networks, Support Vector Machines, and Classification and Regression Trees, that often require more user-intervention, Random Forests tends to yield similar classification accuracies [30,31,33,[36][37][38][39][40]. For these reasons, and because [16] demonstrated its efficacy for classifying shorelines, Random Forests are also evaluated in this research.…”
Section: The Random Forests Classifiermentioning
confidence: 86%
See 1 more Smart Citation
“…It is also relatively simple to implement, requiring little user-intervention; an advantage that is frequently noted [34][35][36]. This is of relevance to this research, since compared to other non-parametric approaches, including Neural Networks, Support Vector Machines, and Classification and Regression Trees, that often require more user-intervention, Random Forests tends to yield similar classification accuracies [30,31,33,[36][37][38][39][40]. For these reasons, and because [16] demonstrated its efficacy for classifying shorelines, Random Forests are also evaluated in this research.…”
Section: The Random Forests Classifiermentioning
confidence: 86%
“…Multiple authors have demonstrated that Random Forests tends to perform better than Maximum Likelihood and other conventional parametric methods [30][31][32][33]. It is also relatively simple to implement, requiring little user-intervention; an advantage that is frequently noted [34][35][36].…”
Section: The Random Forests Classifiermentioning
confidence: 99%
“…It has proven effective for classifying highly dimensional data (i.e., many input variables) from a variety of sensors [23][24][25][26], and has been shown to outperform conventional parametric classifiers, including Maximum Likelihood [23,[27][28][29]. This is particularly relevant with respect to the classification of SAR data, since backscatter values are not typically normally distributed when represented in linear power format [11].…”
Section: The Random Forest Classifiermentioning
confidence: 99%
“…A number of authors have also achieved comparable or improved results with Random Forest, compared to other non-parametric approaches, including Classification and Regression Trees (CARTs) [23,27,30,34], Support Vector Machines [29,[35][36][37], and Neural Networks [29]. These approaches typically require more user-interference with classifier settings whereas Random Forest only requires that users define: (1) the number of trees that are generated; and (2) the number of variables tested during each iteration of node splitting (described subsequently); a benefit that is commonly noted in the literature [24,38,39].…”
Section: The Random Forest Classifiermentioning
confidence: 99%
“…From the data availability aspect, multi-sensor/source data including optical, SAR, and GIS data have been used as inputs for classification [6][7][8][9]. To properly treat input data for classification, advanced classification methodologies such as machine learning approaches and object-based classification Remote Sens.…”
Section: Introductionmentioning
confidence: 99%